[OP.3A.05] THE USE OF PREDICTION SCORE TO DIAGNOSE UNILATERAL DISEASE IN CHINESE PATIENTS WITH PRIMARY ALDOSTERONISM. (September 2016) - Zhang, Y.; Zhnag, H.; Zhou, W.L.; Shen, Z.J.; Xu, J.Z.; Tang, X.F.; Zheng, F.F.; Tao, B.; Zhang, J.; Lu, X.H.; Chu, S.L.; Gao, P.J.; et al.
Abstract : Objective: Küpers et al. 1 had proposed a clinical prediction scores to diagnose unilateral primary aldosteronism (PA). We aim to evaluate this prediction score in Chinese patients with PA. Design and method: 437 patients with PA who had received AVS between 2005 and 2015 were analyzed in this retrospective study. Results: Figure 1 is the flow chart of our patients with PA. According to Küpers' prediction score, the best cutoff value to discriminate unilateral from bilateral disease in our cohort was 4 points. The area under the curve (AUC) of the score was 0.601 (95% CI 0.551–0.650), with the specificity of 53% and the sensitivity of 62%. We then analyzed in 148 patients who were normokalemia during the measurement of 24hour urinary and plasma aldosterone (64 with unilateral disease and 84 with bilateral disease)(Table 1) and modified the prediction score's components by counting the weight of 24hour urinary aldosterone, history of hypokalemia and >  = 1 cm unilateral adenoma size on CT imaging (Table 2). We then found the best cut-off was 5 points with the sensitivity of 45.3% (95% CI 32.8–58.3%) and specificity of 90.5% (95% CI 82.1–95.8%). The AUC of our prediction score was 0.745 (95% CI 0.667–0.813), which is higher than that of Küpers' score (0.635, 95% CI 0.552–0.713) (P = 0.003, Figure 2). Furthermore, according to our prediction score, the best cutoff was 5 points in patients who had right adrenal lesion on CT imaging, with the specificity of 100% (95% CI 71.5–100%) and the sensitivity of 53% (95% CI 26.6–78.7%). In patients younger than 40 years old, the best cutoff was 6 points, with the specificity of 100% (95% CI 75.3–100%) and the sensitivity of 23.5% (95% CI 6.8–49.9%) (Figure 3). Conclusions: Küpers' prediction score is not suitable for Chinese patients with PA. Our modified prediction score can efficiently identify unilateral aldosteronism in patients showing right adenoma on CT and patients younger than 40 years old. Figure. No caption available.